Etika Periklanan, Studi Kasus pada Iklan Grab Bike - Hardi Nugraha Tunggele, Hardi (ISI Press Institut Seni Indonesia Surakarta, 2022)
Advertising is a medium used to offer products to consumers. The great benefits of advertising in attracting consumers make companies compete to create creative advertisements. However, it is possible that the advertisements serve to violate ethics. This research analyzes the ethical values in the #SelectAman advertisement from the Grab Bike company with a critical approach. The perspective used is the ethical dimension by Tanya Robertson, with descriptive qualitative research methods. The selection of the descriptive qualitative method is based on the object of the material being studied and the level of adaptability of this method. The results of the study show that the #PilihAman ad from Grab Bike is a negative and unethical advertisement because it gives a bad picture of competing products